«Epistemological functions of ancient anthroponyms in the modern postmodern novel» - Нев’ярович, Наталя Юріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the problem of specificity of the artistic value and functions of the historical poetonyms in postmodern novel (based on the works by American writer J. Heller "Imagine a picture", Italian novelist U. Eco "The Name of the Rose" and Austrian writer Ch. Ransmayr "The Last World"). The authors advert to such ancient historical figures as Socrates, Aristotle, Ovid, etc. Within the context of post-modern paradigm historical poetonyms carry the function of epistemes of the artistic consciousness while the "transitional period" – doubt, distrust of the authorities, the alternability of the world.